Randomized controlled trial between conventional versus sutureless bioprostheses for aortic valve replacement: Impact of mini and full sternotomy access at 1-year follow-up. (1st December 2022) - Fischlein, Theodor; Caporali, Elena; Folliguet, Thierry; Kappert, Utz; Meuris, Bart; Shrestha, Malakh L.; Roselli, Eric E.; Bonaros, Nikolaos; Fabre, Olivier; Corbi, Pierre; Troise, Giovanni; Andreas, Martin; et al.
Abstract: Background: The present study is a sub-analysis of the multicenter, randomized PERSIST-AVR trial (PERceval Sutureless Implant versus Standard Aortic Valve Replacement) comparing the in-hospital and 1-year results of sutureless versus conventional stented bioprostheses in isolated surgical aortic valve replacement (SAVR) within two different surgical approaches: mini-sternotomy (MS) and full-sternotomy (FS). Methods: A total of 819 patients (per-protocol population) underwent preoperative randomization to sutureless or stented biological valve at 47 centers worldwide. Sub-analysis on isolated SAVR was performed. Results were compared between sutureless and stented within the two different surgical approaches. Results: 285 patients were implanted with Perceval (67% in MS) and 293 with stented valves (65% in MS). Sutureless group showed significantly reduced surgical times both in FS and MS. In-hospital results show no differences between Perceval and stented valves in FS, while a lower incidence of new-onset of atrial fibrillation (3.7% vs 10.8%) with Perceval in MS. After 1-year, use of sutureless valve showed a significant reduction of MACCE (5.2% vs 10.8%), stroke rate (1.0% vs 5.4%), new-onset of atrial fibrillation (4.2% vs 11.4%) and re-hospitalizations (21.8 days vs 47.6 days), compared to stented valves but presented higher rate of pacemaker implantation (11% vs 1.6%). Conclusions: Sutureless bioprosthesis showed significantly reduced procedural times during isolated SAVR in both surgical approaches. Patients with sutureless valves and MS access showed also better 1-year outcome regarding MACCEs, stroke, re-hospitalization and new-onset atrial fibrillation, but presented a higher rate of permanent pacemaker implantation compared to patients with stented bioprosthesis. Highlights: Reduced procedural times for Perceval versus stented valves in AVR randomized trial. Lower 1-year MACCEs rate with Perceval in ministernotomy versus stented valves. Higher pacemaker rate with Perceval versus stented valves in ministernotomy access. No difference between valves for pacemaker rate in full sternotomy approach.